The influence of alloying on Zn liquid metal embrittlement in steels. (15th August 2020) - Scheiber, D.; Prabitz, K.; Romaner, L.; Ecker, W.
Abstract: In this study we investigate Zn liquid metal embrittlement at Fe grain boundaries (GBs) by employing ab initio density functional theory (DFT) simulations. We consider three different GBs and two common alloying elements in steels (Si and Al) and evaluate how the interplay of the elements affects Zn enrichment and embrittlement of the GBs. Our simulations show that Zn has stronger tendency to enrich at both GBs and surfaces than Al and Si. By increasing the amount of Al and Si in the bulk, Zn can be reduced at both GBs and surfaces. This is quantified for a large temperature range by the newly introduced replacement potency, which shows that compared to Al, Si has a larger potency to decrease the amount of Zn at GBs and surfaces. Regarding GB embrittlement, our results demonstrate that Si a small positive, Al a small negative, and Zn a strong negative effect on GB cohesion. In combination with Zn both Al and Si are able to somewhat reduce the detrimental effect of Zn. Graphical abstract: Image, graphical abstract